Modulation of Hsp70 in the Pharmacological Correction of Nervous System Disorders after Pre-natal Hypoxia - Aliyeva, O. H.; Belenichev, I. F.; Popazova, O. O.; Алієва, Олена Геннадіївна; Бєленічев, Ігор Федорович; Попазова, Олена Олександрівна (My University, 2023)
The problem of pharmacologically correcting CNS hypoxic disorders is one of priority. HSP70, an endogenous regulator of cytoprotective processes, can be considered as an effective pharmacological target. The aim of this research was to study the ability of cerebrocurin, angiolin, glutoredoxin, tamoxifen, thiotriazoline, L-arginine, nikomex, HSF-1 and piracetam to modulate the level of HSP70 in the cerebral cortex and blood plasma of rats after prenatal hypoxia (PH).We studied the effect of the drugs on the content of HSP70 in the plasma and neurons (cytoplasmic and mitochondrial fractions) of rat pups on the 30th and 60th day of life in model of chronic hemic PH using the enzyme immunoassay method. It was found that PH leads to the suppression of HSP70 synthesis and to the decrease in its intra- and extracellular levels, with the most significant decrease during the 1st month of life. Drugs course administration demonstrates an increase in intracellular and extracellular levels of HSP70 with a prolonged effect. Cerebrocurin, angiolin, and tamoxifen were the most active modulators of intracellular HSP70. Cerebrocurin, angiolin, and piracetam had the most active effect on the HSP70 content in blood plasma, but the effect of piracitam on the cytosolic and mitochondrial HSP70 fractions was the least of all the drugs studied. Here, we show that cerebrocurin and angiolin were the most effective modulators of HSP70, and their neuroprotective effect deserves further comprehensive study in order to develop methods for effective treatment of hypoxic disorders. HSP70 can serve as a target and marker of hypoxia pharmacological correction.
Keywords: CNS; prenatal hypoxia; HSP70; modulators of HSP70; pharmacological correction; pharmacological target; neuroprotection; neuroprotective drugs; cerebrocurin; angiolin